High Trait Anger, Interpersonal Context, and the Recognition of Anger Problems - Alcazar-Olan, Raul J.; Guzman, Laura Hernandez; Perez, Veronica Reyes; Fragoso, Claudia Gonzalez; Rodriguez, David Jimenez (European Scientific Journal, ESJ, 2017)
Background: High trait anger is usually destructive for individuals and their relationships. This proneness to anger is reflected in frequent angry feelings, for longer periods of time, and with higher levels of physical arousal and negative expressions (e.g., insulting or arguing with others). Unfortunately, not all individuals with high trait anger recognize the problem. Objective: This research assessed the contribution of the interpersonal context (e.g., family members, friends, and boyfriend/girlfriend) to recognize anger problems. Methods: We recruited 192 individuals with high trait anger who completed questionnaires about 1) recognition of anger problems, 2) how they are perceived by others in terms of anger (i.e., â€œbeing irascibleâ€), and 3) if they care about what others think about their anger. Research Design: Cross-sectional. Results: Individuals who recognized their anger problems perceived they have received more messages of â€œYou are very irascibleâ€ from their social contexts, while those who do not recognize anger problems, have received these messages less often. Moreover, the higher the extent to which the individuals care about what other people think or say about their anger (i.e., higher importance attached to messages from others), the more it contributed to a higher recognition of anger problems. In addition, a lower importance attached to such messages was related to a lower recognition of such problems. Recognition of anger problems was higher in participants who had a boyfriend/girlfriend (versus those who did not have one), and in female (versus male) participants.